Innovative concept of design and production of perspective models of tractors of economy class - L. F. Mechkalo (Сельскохозяйственные машины и технологии, 2016)
The authors offered a concept of design and production of tractors perspective models to minimize cost by change of configuration and simplification of cabins for simultaneous safety level increase. Monoblock configuration of tractors presents increased technical difficulties when repair, operation. As a result, financial expenses increase and use efficiency decrease. One of the main tasks facing designers is providing the corresponding working conditions, decrease in vibration influences, physical activities that reduces fatigue of the operator and increases labor productivity. A technical solution of a problem of increase of efficiency of the Russian agrarian and industrial complex is creation of the agricultural tractor which is not only most adapted for the Russian conditions, but also having competitive advantages. The authors offered the concept of a new tractor with know-how elements which main differences are: shift of the engine forward on the level of regular freights, rigid fixing of an arch or safety small frame on a tractor frame. The runner block with a control platform is mounted inside of this frame. Thus the cabin made of various materials providing necessary noise and thermal insulation is mounted onto the runner block. Possibility of achievement of the specified purpose is illustrated in this paper by the example of a caterpillar.